(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Obesity is a great concern for one and all. Its increasing rate in developing country leading to epidemic as the dietary habits of Asians have been westernized rapidly in past few years. The present case report evaluates the efficacy of Medohar guggulu kalp chikitsa in obese patient. A 49 years old man came with complaint of increase weight from last 3 years and pain in bilateral knee joints for 6 months. Though Ayurveda advocates the different modalities of treatment in Obesity viz., Sthaulya. In present case, Kalp chikitsa with Medohar guggulu was administered to patient for 10 days followed by structured diet for another 10 days. The patient responded well to prescribed treatment and effective results were achieved. Patient lost 9.5kg of weight in 20 days without any complications. This unique ancient modality of treatment could be boon for managing lifestyle disorders and also to reprieve the ill effects of condition in long term